2012
DOI: 10.1188/13.onf.22-29
|View full text |Cite
|
Sign up to set email alerts
|

Developing Emotional Intelligence Ability in Oncology Nurses: A Clinical Rounds Approach

Abstract: Few research studies have explored development of emotional intelligence abilities in clinical staff nurses. Evidence from this study suggests that interventions in the clinical environment may be used to develop emotional intelligence ability. Impact from such development may be used in the future to not only improve the quality of nursing care, but also potentially limit the negative effects of high-stress environments on nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
1
32
0
1
Order By: Relevance
“…Some have been aimed at addressing compassion fatigue and grief resolution, such as a compassion fatigue resiliency program (Potter et al, 2013), compassion fatigue training (Walton & Alvarez, 2010), a compassion fatigue and cumulative grief education intervention (Houck, 2014), and grief resolution (Hildebrandt, 2012). Others have been aimed at psychological and emotional support, such as "care for the professional caregiver" programs (Edmonds et al, 2012), support groups (Wittenberg-Lyles, Goldsmith, & Reno, 2014), psychological skills training (Traeger et al, 2013), and emotional intelligence rounds (Codier, Freitas, & Muneno, 2013). Some studies have focused on mindfulness-based stress reduction (Potter et al, 2010;Schieszer, 2014;Traeger et al, 2013) and mindful awareness group-focused work (Todaro-Franceschi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some have been aimed at addressing compassion fatigue and grief resolution, such as a compassion fatigue resiliency program (Potter et al, 2013), compassion fatigue training (Walton & Alvarez, 2010), a compassion fatigue and cumulative grief education intervention (Houck, 2014), and grief resolution (Hildebrandt, 2012). Others have been aimed at psychological and emotional support, such as "care for the professional caregiver" programs (Edmonds et al, 2012), support groups (Wittenberg-Lyles, Goldsmith, & Reno, 2014), psychological skills training (Traeger et al, 2013), and emotional intelligence rounds (Codier, Freitas, & Muneno, 2013). Some studies have focused on mindfulness-based stress reduction (Potter et al, 2010;Schieszer, 2014;Traeger et al, 2013) and mindful awareness group-focused work (Todaro-Franceschi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the overwhelming positive findings, the review identified some mixed effects. One study (Codier, Freitas, & Muneno, 2013) did not reveal any difference in nurse turnover after an intervention to increase EI. Interestingly, another study (Newton, Teo, Pick, Ho, & Thomas, 2016), revealed mixed-effects of EI, with some nurses with low EI buffered against psychological stress.…”
Section: Ei and Burnoutmentioning
confidence: 96%
“…Codier et al, using an experimental design, showed that an EI intervention program increased nursing staff's documentation of patient emotional status (Codier et al, 2013). However, one study (Chao et al, 2016) was underpowered to determine if EI affected the quality of care provided by nurses (as assessed via a patient questionnaire).…”
Section: Ei and Quality Of Carementioning
confidence: 99%
“…Chemiss and Adler (2000) note that, although people do not inherently possess Goleman's five dimensions of emotional intelligence, EI can be learned, although such an effort is not easy or linear. A number of studies indicate the effectiveness of EI training for children, adolescents, college students, and nurses (e.g., Codier, Freitas & Muneno, 2013;Motamedi, Ghobari-Bonab, Beh-pajooh, Yekta, & Afrooz, 2017;Orak, Farahani, Kelishami, Seyedfatemi, Banihashemi, & Havaei, 2016;Ulutas & Ömeroglu, 2007). More relevant to the study at hand, Clarke (2010) finds that a one-day EI training has no impact on MBA students, but when the training is followed by intensive team-based learning, the EI dimension of relationship management significantly increases.…”
Section: Emotional Intelligencementioning
confidence: 99%